Análise sistemática de aplicação de métodos ágeis em ambientes empresariais e institucionais - ALMEIDA, Adrielle Veras de (2019)
Currently, the software is practically indispensable, since it was developed to speed up services that, once, were done manually. As a result of this, diverse software development methodologies have emerged, with the aim of making the system production process organized and standardized and offering customers a higher quality product. This monograph deals with the use of agile methodologies for the development of software and has the objective of analyzing the contributions of this methodology in organizations and institutions, through the bibliographic review combined with some practices of the systematic review of the literature, applied to studies produced on the subject, in the period from 2010 to 2018. For the accomplishment of this monograph 570 papers were mapped, disseminated in digital databases that were later filtered from predefined criteria for the analysis and discussion of the data. Based on the research, it was verified the need to know the agile methodologies before adopting them, in order to verify which alternative / option is best suited to the organization of a given project, in order to achieve the desired objective. Thus, the results obtained in this monograph validate the agile methodologies to accelerate the software development process, through aspects such as: targeted planning, objectivity and short-term production of products takes care the real customer needs.